[The Chinese massacre ; Ecotourism in Palawan ; The Irreverent Leo [videorecording] - Lazaro, Cheche (The Probe Team ; [episode no.213], 1992)
An investigative report on Chinese community being singled out for kidnapping for ransom. The opening of Palawan to tourists yet preserving its beauty. Interview with Leo, the next superstar comedian.